Renewal of Patents and Government Financing - Roger Svensson (Research Institute of Industrial Economics (IFN), 2008)
I apply a survival model to a detailed dataset of Swedish patents to estimate how different factors affect the likelihood of patent renewal. Since the owners know more about the patents than potential external financiers, there is a problem of asymmetric information. To overcome this, Sweden has for a long time relied on government support rather than private venture capital. The empirical results show that patents which have received soft government financing in the R&D-phase have a higher probability of expiring than patents without such financing. But patents that have received more market-oriented government loans during the commercialization phase are renewed for as long as other commercialized patents. This finding indicates that it is the financing terms rather than bad choices of projects that explain the low renewal of patents with government financing.
Keywords: G30; O34; O38; 330; Patents; Renewal; Government Financing; Survival Model; Forschungs- und Technologiepolitik; Patentrecht; Forschungssubvention; Risikokapital; Patent; Asymmetrische Information; Schweden